Sejarah sebagai Sekolah Moral Versus Supermarket Sekolah Abad XXI dan Memudarnya Kesejatian Hidup - Nengah Bawa Atmadja (Jurnal Kajian Bali (Journal of Bali Studies), 2014)
AbstractThis article reviews the phenomenon of modern education, particularly highlighting the behavior ororientation of society that ignores history as a school of moral or political virtue in society and state. Without the presence of the government so that the symptom slooping symbolic violence. Second, look for strategic steps that can be done so that the function of history as amoral school optimal.Kajian can run against both of these issues are very fundamental and must be understood as the historical background of the dysfunctional moral school. School morale is an important part of finding a solution. By using the approach of cultural studies, the teaching of history can be directed and contributed ideal text and social text in order to overcome various problems.